Faktor-Faktor Risiko Terjadinya Berat Bayi Lahir Rendah - Lydia Febrina; Triana Sri Herdjanti; Siti Nikmah (Poltekkes Kemenkes Jakarta III, 2019)
Low Birth Weight (LBW) is the proportion of live births weighing less than 2,500 grams and 20 times the chance of dying in infancy. LBW is the result of premature birth (<37 weeks' gestation) or impaired intrauterine growth. Neonatal mortality is one of the indicators determining the health and welfare of children. IMR in Banjarnegara Regency in 2015 was 13.23 per 1,000 live births which in absolute terms still ranked highest in Central Java Province. The formulation of the problem is risk factors of low birth weight at Karang Kobar Health Center in Banjarnegara Regency in 2018. This research is a descriptive analytic study using case control study design. The research sample was taken from the total number of LBW in January to December 2017. Data were analyzed univariate and bivariate. The results of the study, the factors associated with the incidence of LBW are the factors of maternal age during pregnancy, gestational age, anemia, and nutrition pregnant women.